2014
DOI: 10.1097/hjh.0000000000000186
|View full text |Cite
|
Sign up to set email alerts
|

KCNJ5 gene somatic mutations affect cardiac remodelling but do not preclude cure of high blood pressure and regression of left ventricular hypertrophy in primary aldosteronism

Abstract: Compared to the wild-type APA patients those with KCNJ5 mutations showed more prominent cardiovascular damage. Notwithstanding this, their chances of being cured from the hyperaldosteronism and the high BP, and of regression of left ventricular hypertrophy after adrenalectomy, were not compromised by the presence of these mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 34 publications
2
45
0
1
Order By: Relevance
“…The concentration gradient of K C between the intracellular and extracellular space that is required for the establishment of the membrane potential is generated by the activity of the Na C , K C -ATPase. Elevation of extracellular K C concentration; decrease in intracellular K C concentration; inhibition of the Na C , K C -ATPase, or potassium channels all lead to cell membrane depolarization, previously reported in other cohorts (Azizan et al 2013, although KCNJ5 mutations may be more or less frequent in certain populations (Kitamoto et al 2014, Rossi et al 2014. In particular, it has been shown that the frequency of KCNJ5 mutations is higher in patients selected on more conservative criteria to define successful cannulation and lateralization during adrenal venous sampling than in centers adopting more permissive indices (Boulkroun et al 2012).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The concentration gradient of K C between the intracellular and extracellular space that is required for the establishment of the membrane potential is generated by the activity of the Na C , K C -ATPase. Elevation of extracellular K C concentration; decrease in intracellular K C concentration; inhibition of the Na C , K C -ATPase, or potassium channels all lead to cell membrane depolarization, previously reported in other cohorts (Azizan et al 2013, although KCNJ5 mutations may be more or less frequent in certain populations (Kitamoto et al 2014, Rossi et al 2014. In particular, it has been shown that the frequency of KCNJ5 mutations is higher in patients selected on more conservative criteria to define successful cannulation and lateralization during adrenal venous sampling than in centers adopting more permissive indices (Boulkroun et al 2012).…”
Section: Figurementioning
confidence: 99%
“…Mutations result in gating changes suggesting gain-offunction mutations, in particular a shift of voltagedependent channel activation to more negative voltages, or to reduced inactivation of the channel, depending on the mutation, leading, similarly to ATP2B3 mutations, to alterations in intracellular calcium homeostasis. Different studies have established the frequency of somatic mutations in cohorts with at least 100 patients with APA (Akerstrom et al 2012, Boulkroun et al 2012, Azizan et al 2013, Fernandes-Rosa et al 2014, Kitamoto et al 2014, Rossi et al 2014. Among them, two subsequent multicenter studies, performed within the European Network for the Study of Adrenal Tumors (ENS@T, www.ensat.org), have investigated the genetic spectrum and clinical correlates of somatic mutations in APA (Boulkroun et al 2012, Fernandes-Rosa et al 2014.…”
Section: Somatic Mutations In Apamentioning
confidence: 99%
“…Intriguingly, recent observations showed that KCNJ5 mutation carriers might exhibit a more florid phenotype with younger age, 13,14 higher aldosterone level, 13,14 and prominent cardiac damage. 15 Currently, there has not been agreement on the correlation between KCNJ5 mutations and response to adrenalectomy. 15,16 Therefore, a greater number of cases need to be studied to evaluate the clinical characteristics of patients with and without somatic mutations in APAs.…”
mentioning
confidence: 99%
“…15 Currently, there has not been agreement on the correlation between KCNJ5 mutations and response to adrenalectomy. 15,16 Therefore, a greater number of cases need to be studied to evaluate the clinical characteristics of patients with and without somatic mutations in APAs. There has been no study investigating somatic mutations in APAs in China thus far.…”
mentioning
confidence: 99%
“…Les mutations KCNJ5 sont les anomalies génétiques les plus fréquentes (prévalence de 38 %) ; les mutations ATP1A1 et ATP2B3 sont présentes respectivement dans 5,3 % et 1,7 % des adénomes produisant de l'aldostérone. La fréquence de ces mutations concorde avec celle rapportée à partir d'autres cohortes [9,11,16], bien que les mutations KCNJ5 soient plus ou moins fréquentes dans certaines populations et selon les procédures diagnostiques utilisées [14,17,18]. Les mutations du gène CACNA1D sont les secondes mutations les plus fréquentes après les mutations KCNJ5 et leur prévalence est de 9,3 % [15].…”
Section: Anomalies De Kcnj5 Dans L'hyperaldostéronisme Primaire Familialunclassified